Medical education and academic traditions in universities and institutes of European countries through the eyes of professors, teachers and staff of the Imperial Tomsk University (1902-1914) - Nekrylov, Sergei A. (History of medicine)
This article analyses reports on trips abroad made by professors, privatdozents, laboratory assistants and prosectors from the Imperial University of Tomsk to European countries in the period from 1902 to 1914. It examines the difficulties they faced on their visits "for research purposes" to Europe. It is emphasised that maintaining contacts with colleagues abroad was one of the key priorities for representatives of the pre-revolutionary academic community in Tomsk. The Russian academics' observations also focused on the teaching methods used in the courses taught by leading professors from universities and institutes in Berlin, Breslau, Paris, Freiburg, Tübingen, Zürich, and so on, the contents of the lectures, the relationship between theory and practice in the educational process, and the comparative features of the mentality of foreigners and Russians. Following a comparative historical analysis, it is concluded that, despite the superiority of European university-level medical education in the period, Russians academics not only enjoyed successes in this field, but also took a critical view of the content of individual courses (legal medicine, the absence of toxicology in the programmes, etc.), the students' general preparation, and the state of hospitals and individual laboratories (in particular, the physiological laboratory at the Pasteur Institute in Paris, etc.). At the same time, the reports studied represent the experience of mapping the biggest centres of science and education in the fields of hygiene and bacteriology, surgery and ophthalmology, legal medicine and pathological anatomy, and so on. They also reflect the particular features of the development of the medical systems of Russia and Europe, which were then part of a single "academic ecumene", shown most clearly in attitudes to academic tradition and the participation of Professor Aleksei Kulyabko of the University of Tomsk in anniversary celebrations at Trinity College Dublin in 1912 and at the University of Groningen in 1914. © SA Nekrylov, AO Stepnov, SF Fominykh.